Short-Term and Long-Term Effects of Bariatric Surgery on Diabetic Retinopathy: A Systematic Review - Erika Butkutė; Monika Zieniūtė; Agnė Morkūnaitė; Vilma Jūratė Balčiūnienė (Medicina)
Background and Objectives: Diabetic retinopathy (DR) is a common diabetes complication and a leading cause of blindness. Although bariatric surgery (BS) is well studied for diabetes management, its effects on DR onset and progression, particularly long-term outcomes, remain underexplored. This review seeks to evaluate the short- and long-term retinal outcomes of BS in diabetic patients. Materials and Methods: A systematic search of PubMed, Web of Science, and Cochrane Library was conducted following PRISMA 2020 guidelines, including the use of the PRISMA checklist and flow diagram. The search included English-language articles (2014–2024) using keywords like “diabetic retinopathy” and “bariatric surgery”. The review excluded studies published in languages other than English, as well as reviews, case reports, and those lacking adequate data or relevance. The risk of bias was determined by using the Downs and Black checklist. A systematic review of the literature was conducted, and the results were organized and displayed in tables to summarize and compare the main findings. Results: After screening 158 articles, 13 studies involving 17,903 patients were selected, focusing on the effects of BS on DR progression and regression. Short-term data suggest that BS may stabilize or improve DR but poses risks of worsening in advanced cases, requiring careful monitoring. However, long-term findings are inconsistent, with evidence of both DR regression and progression. These variations highlight the need for further research. Discussion: BS generally improves DR progression, but its effect depends on preoperative severity and glycemic control. Further studies should explore additional risk factors to better predict DR outcomes post-surgery. Conclusions: BS improves weight management, blood pressure, and diabetes control, potentially benefiting DR. However, the long-term effects remain uncertain due to conflicting findings. Rapid glycemic changes after surgery may pose risks of DR progression. Large-scale, longitudinal studies are needed to clarify the role of BS in DR progression and regression.